2011
DOI: 10.1007/s10103-011-0998-7
|View full text |Cite
|
Sign up to set email alerts
|

The impact of antimicrobial photodynamic therapy in an artificial biofilm model

Abstract: The susceptibility of bacterial cultures in biofilm formations is important for a variety of clinical treatment procedures. Therefore, the aim of the study was to assess the impact of laser-induced antimicrobial photodynamic therapy on the viability of Streptococcus mutans cells employing an artificial biofilm model. Using sterile chambered coverglasses, a salivary pellicle layer was formed in 40 chambers. Streptococcus mutans cells were inoculated in a sterile culture medium. Employing a live/dead bacterial v… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
27
0
8

Year Published

2012
2012
2022
2022

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 50 publications
(38 citation statements)
references
References 27 publications
(29 reference statements)
2
27
0
8
Order By: Relevance
“…This suggests that a posttreatment decrease in green fluorescence signals can be proportionally attributed to photosensitizer incorporation within the bacterial cells rather than to competitive inhibition, namely, the interference of TB or Ce6 with the binding of the live/dead dyes to intracellular targets. A similar tendency was also shown in several in vitro reports concerning the application of various APDT methods and photosensitizers to bacteria (51)(52)(53). Nevertheless, Pfitzner et al interpreted their contradictory results as resulting from the presence of fluorescent photosensitizers, which possibly make the measured number of nonvital microorganisms stained with SYTO 9 -PI inaccurate (46).…”
Section: Discussionsupporting
confidence: 62%
“…This suggests that a posttreatment decrease in green fluorescence signals can be proportionally attributed to photosensitizer incorporation within the bacterial cells rather than to competitive inhibition, namely, the interference of TB or Ce6 with the binding of the live/dead dyes to intracellular targets. A similar tendency was also shown in several in vitro reports concerning the application of various APDT methods and photosensitizers to bacteria (51)(52)(53). Nevertheless, Pfitzner et al interpreted their contradictory results as resulting from the presence of fluorescent photosensitizers, which possibly make the measured number of nonvital microorganisms stained with SYTO 9 -PI inaccurate (46).…”
Section: Discussionsupporting
confidence: 62%
“…As it is known, bacteria in a biofilm are better protected from antimicrobial approaches. In a recent publication by Schneider et al the penetration of an ex vivo biofilm by the PS phenothiazine chloride was observed. It was found, that there is a decrease in available PS from the top to the bottom of the biofilm.…”
Section: Discussionmentioning
confidence: 98%
“…Moreover, recent studies have reported that photodynamic therapy induced bacterial cell killing and reduced bacterial numbers by more than tenfold in S. mutans, Streptococcus sobrinus, and Streptococcus sanguinis biofilms when toluidine blue O or erythrosine was used as the photosensitizer [82][83][84][85]. Schneider et al [86] assessed the effect of laser-induced antimicrobial photodynamic therapy on the viability of S. mutans cells employing an artificial biofilm model and concluded that laser irradiation is an essential part of antimicrobial photodynamic therapy to reduce bacteria within a layer of 10 μm.…”
Section: Antimicrobial Photodynamic Therapy and Periodontologymentioning
confidence: 98%